Consumer engagement dynamics through SST and IoT innovations in diverse markets - Ajayi, S.; Loureiro, S. M. C.; Langaro, D. (AMA conference proceedings: AMA Summer Academic Conference 2024, 2024)
Purpose - This study aims to examine the impact of IoT and self-service technology on consumer engagement by analyzing the mediating role of satisfaction, quality of alternatives, relationship investment, customer emotions on commitment with perspectives from Nigeria and USA.